Perancangan Sistem Pompa Irigasi Pembangkit Listrik Tenaga Surya (PLTS) Untuk Pertanian Subak Semaagung - Oya Iman Sanjaya; IAD Giriantari; I N Satya Kumara (Jurnal SPEKTRUM, 2019)
In general the average rice harvest in Indonesia is three times in one year with a rice age of 115-120 days. Subak is an organization owned by farmers in Bali that specifically regulates traditional rice field irrigation systems. Subak Semaagung every year there is a shortage of water on agricultural land. Subak area of approximately 55 hectares consisting of six groups of farmers called "tempek". Agricultural water supplied to each tempek interchangeably because the water supply is very limited, so any tempek can only grow rice once in 2 years. The situation is very difficult for farmers to maintain their own rice fields with a limited water supply, so that the fields in the Subak has been largely abandoned. Previously, the Ministry of Agriculture has provided assistance in the form of diesel-powered irrigation pump system, but the diesel-powered water pumping systems are only used for 1 year because it requires a very complicated way of operational and fuel costs are enormous. This research will be designed water pump system Solar Power Plant (PLTS) for more effective than previous diesel pump. From the discussion and analysis has been done that with an area of 300 m2 can be mounted solar panels monokristaline 52.14 kW with a maximum capacity of solar modules totaling 158 units, inverter 33 kW two units, and Submersible pumps SP 60-9 two units. So that the result of the calculation of water that can be lifted inthe dry season every day is 1.275.000/liters/day. With a total investment cost of solar power water pumps Subak Semaagung ????????1.168.137.010.